1982
DOI: 10.1080/00288330.1982.9515958
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics and fishery management of the paua,Haliotis irisI. Population structure, growth, reproduction, and mortality

Abstract: The biology of an unfished population of the paua, Haliotis iris Martyn, in Peraki Bay, Banks Peninsula, was studied from 1973 to 1976. In February 1976 the population consisted of about 179 000 animals on 4.5 km of coastline. The length/frequency distribution was strongly skewed to the left, indicating an accumulation of old individuals and a recent history of low recruitment. Growth of animals <70 mm long was determined from changes in length frequency, and of larger animals by the analysis of tag returns. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
2
2

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 16 publications
8
62
2
2
Order By: Relevance
“…This is considered unlikely because the density of juveniles from the shallow habitat is the highest recorded for the species (McShane et al 1994). The low levels of recruitment of H. iris observed in our study is consistent with results obtained by Sainsbury (1982) which he attributed to natural recruitment failure. Furthermore, surveys of juvenile habitat off southern New Zealand (> 41°S) found no juvenile H. iris at more than 60% of the 300 sites searched (McShane 1993, unpubl.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This is considered unlikely because the density of juveniles from the shallow habitat is the highest recorded for the species (McShane et al 1994). The low levels of recruitment of H. iris observed in our study is consistent with results obtained by Sainsbury (1982) which he attributed to natural recruitment failure. Furthermore, surveys of juvenile habitat off southern New Zealand (> 41°S) found no juvenile H. iris at more than 60% of the 300 sites searched (McShane 1993, unpubl.…”
Section: Discussionsupporting
confidence: 82%
“…The perimeters of crosssections of gonad and digestive glands were traced onto paper with the aid of a dissecting microscope equipped with a camera lucida, and their areas were used to calculate a macroscopic gonad index by sex (Shepherd & Laws 1974). This procedure has been successfully used in previous studies of reproduction in H. iris (Poore 1973;Sainsbury 1982).…”
Section: Reproductive Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Decreased growth rate appears not just to be the result of general decline in metabolism among older animals, but rather to be at least partly due to the competitive demand of the gonad for energy. In support of this, a number of authors have reported decreased growth rates for abalone specifically during periods of gonad production (Shepherd and Heam, 1983;Keesing and Wells, 1989), and negligible growth during most of the year except for a growth spurt after spawning (Cox, 1962;Foster, 1967;Poore, 1972;Sainsbury, 1982;Keesing and Wells, 1989). The present study took place over 10 weeks from April to July, which corresponds to the time of gametogenesis and negligible somatic growth in H. hmtschatkuna (Paul et al, 1976).…”
Section: Discussionmentioning
confidence: 89%